Guest

if a.sinA = b.cosA = 2c/(1-tanA^2) prove that (a^2-b^2)^2 = 4c^2(a^2+b^2)

if a.sinA = b.cosA = 2c/(1-tanA^2) prove that (a^2-b^2)^2 = 4c^2(a^2+b^2)

Grade:11

2 Answers

Saurabh Koranglekar
askIITians Faculty 10335 Points
2 years ago
Dear student

There are 4 variables and 3 equations kindly check the question

Regards
Vikas TU
14149 Points
2 years ago
Dear student 
Question is not clear 
Please attach an image, 
We will happy to  help you 
Good Luck
Cheers
 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free